Gilbert cell down-conversion mixer for THz wireless communication with passive baluns - Abdeladim El Krouk; Abdelhafid Es-saqy; Mohammed Fattah; Said Mazer; Mahmoud Mehdi; Moulhime El Bekkali; Catherine Algani (Universitas Ahmad Dahlan, 2024)
This article presents the design of an active down-conversion mixer for the superheterodyne receiver system for 6G wireless communications. This mixer is developed based on the Gilbert cell in the terahertz frequency band, using the PH15 transistor from United Monolithic Semiconductors (UMS) Foundry in monolithic microwave integrated circuit (MMIC) technology. We used the charge injection method to increase our mixer’s conversion gain. In addition, we integrated a buffer stage at the mixer outputs to facilitate impedance matching and improve linearity. The power dividers used in this chapter are based on transmission lines from Agilent's advanced design system (ADS) tool, connected to the input and output ports of the circuit. The proposed architecture offers a high conversion gain of 15.2 dB, with a low local oscillator (LO) power of 0 dBm, a low double sideband (DSB) noise figure (NF) of around 7.1 dB, a 1 dB compression point of -16 dBm, and good radio frequency (RF)-LO port isolation of 63.2 dB, at a RF of 0.14 THz.